DETERMINAN KINERJA KEUANGAN PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Maheswari Cahyarani Widyadana (2021)
The purpose of this research is to determine the factors that can affect the Bank's financial performance projected with Return on Assets (ROA), including Credit Risk with Non Performing Loans (NPL), Liquidity with Loan to Deposit Ratio (LDR), and Adequacy. Capital with Capital Adequacy Ratio (CAR) in 36 Conventional Commercial Banks that have been listed on the IDX with the observation period 2017 to 2019. The research method used is panel data regression analysis using the help of the Eviews 10. The results of the study state that (1) Credit Risk has a negative and significant effect on financial performance, (2) liquidity has a positive and significant effect on financial performance, and (3) capitals has a negative and significant effect on financial performance.